Balneários castrejos do Noroeste Peninsular : notícia de um novo monumento do Castro de Roques - Silva, Armando Coelho F.; Maciel, Tarcísio Daniel P. (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Notice of the identification of a new indigenous bath structure in the Castro of Roques, Lima Valley, regarding the discussion of this finding about the location, chronology, typology and function of these protohistoric monuments of the peninsular Northwestern Castro’s Culture.